Analisis Postur Kerja di UKM Ismail Ali Menggunakan Metode NBM, REBA, dan OWAS - Muhammad Abdul Basit; Elly Ismiyah (G-Tech: Jurnal Teknologi Terapan, 2025)
In Gresik Regency, there are SMEs such as Ismail Ali that sell products such as cement. In lifting and arranging cement, manual material handling is carried out. As a result, workers are at risk of back injury whose activities are not ergonomically appropriate, musculoskeletal disorders can arise. From these activities, the NBM analysis was carried out to determine the source of pain obtained on a Likter scale of 3 in the high risk level, the REBA method by involving the angle of the worker's posture obtained a score of 11 in the very high category, and the OWAS method by examining the effect of the load on the posture obtained a score of 3 in the high category. This research shows that lifting and arranging cement in Ismail Ali SMEs has a high risk of musculoskeletal disorders, seriously affecting health and work productivity. The results of the analysis using the NBM, REBA, and OWAS methods, found that non-ergonomic work positions cause serious injuries if not addressed immediately. Therefore, industries need to implement corrective measures such as scheduled breaks, stretching, improved work postures, worker rotation to reduce the risk of injury, increase efficiency, and prevent human error due to fatigue.